Studying moisture transport trough "active" fabrics using humidity-temperature sensor nodes - Koptyug, A.; Bäckström, M.; Nilsson, K.; Ainegren, M. (Proceedings, 2018)
Active fabrics providing better comfort of the garments and footwear rapidly become an essential part of our life. However, only limited information about the performance of such fabrics is commonly available for the garment and footwear designers, and tests are often done only with the final products. Thus development of the objective testing methods for the fabric assemblies containing microporous membranes and garments using them is one of the important topics. Garment tests in the climate chamber when exercising in windy and rainy conditions with a set of temperature and humidity sensors placed over the body allow comparing manufactured garments for thermal and humidity comfort. To allow for better material testing a new laboratory setup was developed for studying the dynamics of the humidity transport through different fabrics at realistic conditions in extension of the existing ISO test procedure. Present paper discusses the experimental procedures and first results acquired with new setup.